2011
DOI: 10.3989/scimar.2011.75n4779
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the sequential geographical exploitation and potential collapse of marine fisheries through economic globalization, climate change and management alternatives

Abstract: SUMMARY: Global marine fisheries production has reached a maximum and may even be declining. Underlying this trend is a well-understood sequence of development, overexploitation, depletion and in some instances collapse of individual fish stocks, a pattern that can sequentially link geographically distant populations. Ineffective governance, economic considerations and climate impacts are often responsible for this sequence, although the relative contribution of each factor is contentious. In this paper we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The consequence of this is that strict fisheries management and market stabilization measures will be crucial to ensure the sustainability of fisheries dedicated to fishmeal and oil production. Thus management systems need to be sufficiently robust to control fishing mortality despite increasing demand (Berkes et al, 2006;Merino et al, 2011;O'Brien and Leichenko, 2000). While some recent management efforts have led to improved controls of fishing mortality, along with stock stabilization and recovery in some places (Branch et al, 2011;Worm et al, 2009), some small pelagic fisheries continue to be sub-optimally managed and sensitive to demand changes (Asche and Tveterå s, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The consequence of this is that strict fisheries management and market stabilization measures will be crucial to ensure the sustainability of fisheries dedicated to fishmeal and oil production. Thus management systems need to be sufficiently robust to control fishing mortality despite increasing demand (Berkes et al, 2006;Merino et al, 2011;O'Brien and Leichenko, 2000). While some recent management efforts have led to improved controls of fishing mortality, along with stock stabilization and recovery in some places (Branch et al, 2011;Worm et al, 2009), some small pelagic fisheries continue to be sub-optimally managed and sensitive to demand changes (Asche and Tveterå s, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…It was found that coastal low-income food deficit countries (LIFDC) are heavily dependent on fish catches as a way of meeting their nutritional needs but almost every coastal LIFDC is in danger of decrease in fisheries maximum revenue potential. Merino et al (2011) examined the synergistic effect of climate variability and production of fish with estimation of maximum sustainable yield. They put emphasis on global management measures to achieve optimized global supply of marine products, suggesting interaction between global markets and regional climate may be acting as a factor causing sequential overexploitations and resource depletion.…”
Section: Economic Review On Impacts Of Climate Change On Fisheriesmentioning
confidence: 99%
“…For example, if stock biomass declines because of climate shifts, catches will also eventually decline and this scenario will also be interpreted as overfishing and collapse in the SSP (e.g. Peruvian anchoveta, Engraulis ringens, Engraulidae, Bakun and Weeks 2008;Arias-Screiber et al 2010;Merino et al 2011). A good number of fisheries in coastal regions (mainly in developed countries) progressed to tighter regulations to either prevent collapse or in response to a significant decline in landings, usually attributable to heavy exploitation.…”
Section: Open-access and Regulated Fisheriesmentioning
confidence: 99%
“…Peruvian anchoveta, Engraulis ringens , Engraulidae, Bakun and Weeks 2008; Arias‐Screiber et al. 2010; Merino et al. 2011).…”
Section: Expected Ssp Performance Under Various Scenariosmentioning
confidence: 99%